HUBUNGAN JENIS KELAMIN TERHADAP KEBERSIHAN RONGGA MULUT ANAK PANTI ASUHAN - Diana Setya Ningsih (Faculty of Dentistry, Universitas Islam Sultan Agung, 2015)
Background: Dental health of child is a reflection of a healthy life of their future. It is strongly influenced by the child's oral hygiene which can be seen from the index of OHIS (oral hygiene index simplified). The level of oral hygiene in general is influenced by their gender and parents. Purpose: This study aimed to assess the effect of gender on children's oral hygiene at the orphanage.Method: This research was conducted at the orphanage Al Ishlah Al Aziziyah Banda Aceh with randomly selected subject by quota sampling technique. The subject of this study was 76 people (boy = 38 people and girl = 38 people). Subjects were applied by disclosing solution for 5 minutes and then recorded a score of debris and calculus using the index proposed by Greene and Vermillion. the value of debris and calculus were summed to obtain the index of OHIS. Result: The results showed the level of dental hygiene of the girls are much better than the level of oral hygiene of the boys (p<0.05). Conclusion: It was concluded that gender affects oral health of children.